Nullity of the matrimony because of the absence of true matrimonial consent - Olivares D'Angelo, S.J., Estanislao (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
The concept of matrimonial consent proposed by the new Code of Canon Law includes more elements than the concept of matrimonial consent of the abrogated Code. Because of that, it is necessary to reflect on the causes of nullity, that because of the defect of consent the actual Code proposes, and to check out whether it takes into consideration all the causes of invalid matrimonial consent, which are inferred from the renewed matrimonial consent, that it proposes. To that end, the defects of consent by error, condition, force and fear, ignorance and simulation, are reconsidered.